Le jardinage amateur comme modèle pour une imagerie de l’espace public contemporain ? - Aurélien Ramos (Projets de Paysage)
How can the interest of French municipalities in recent years for informal and amateur gardening practices in public spaces be explained? Photographed and compiled by local authorities, these practices fundamentally renew the imagery of contemporary public spaces by introducing aesthetics previously confined to the private domestic garden. Based on the cases of the cities of Angers, Marseilles, Nantes and Paris, this article looks at the development of images of amateur gardening practices in public spaces, disseminated on the websites of these municipalities and on Instagram. Based on this institutional and participatory body of images, the objective is to understand whether municipalities should develop, on the basis of these informal and amateur practices, a new model by which amateur gardeners would become a means of producing public spaces. We will see to what extent this imagery serves a much broader set of objectives than the beautification of public spaces and contributes to establishing dynamics of imitation and distinction between citizen gardeners.